A Generalized Framework for the Study of Spinal Motor Neurons Controlling the Human Hand During Dynamic Movements - Cakici, Andre L.; Oßwald, Marius; Souza de Oliveira, Daniela; Braun, Dominik; Simpetru, Raul C.; Kinfe, Thomas Mehari; Eskofier, Björn; Del Vecchio, Alessandro (Proceedings of the Annual International Conference of the IEEE Engineering in Medicine and Biology Society, EMBS, 2022)
The human hand possesses a large number of degrees of freedom. Hand dexterity is encoded by the discharge times of spinal motor units (MUs). Most of our knowledge on the neural control of movement is based on the discharge times of MUs during isometric contractions. Here we designed a noninvasive framework to study spinal motor neurons during dynamic hand movements with the aim to understand the neural control of MUs during sinusoidal hand digit flexion and extension at different rates of force development. The framework included 320 high-density surface EMG electrodes placed on the forearm muscles, with markerless 3D hand kinematics extracted with deep learning, and a realistic virtual hand that displayed the motor tasks. The movements included flexion and extension of individual hand digits at two different speeds (0.5 Hz and 1.5 Hz) for 40 seconds. We found on average 4.7-1.7 MUs across participants and tasks. Most MUs showed a biphasic pattern closely mirroring the flexion and extension kinematics. Indeed, a factor analysis method (non-negative matrix factorization) was able to learn the two components (flexion/extension) with high accuracy at the individual MU level (R=0.87-0.12). Although most MUs were highly correlated with either flexion or extension movements, there was a smaller proportion of MUs that was not task-modulated and controlled by a different neural module (7.1% of all MUs with R < 0.3). This work shows a noninvasive visually guided framework to study motor neurons controlling the movement of the hand in human participants during dynamic hand digit movements.
CRIS-Team Scopus Importer:2022-10-14